Production Model Based on Lean Tools and SLP to Increase Labor Productivity in Companies in the Food Industry - Huarcaya Melendez, Valeria (2023)
The Peruvian food industry plays a crucial role in the country's economy, but it faces a major challenge in the form of low labor productivity. This problem not only hinders the industry's growth but also negatively impacts company profits. This study proposes a model for improvement using SLP and Lean tools to address the underlying causes of low labor productivity in a Peruvian food industry company. The objective of this research is to enhance labor productivity and achieve or surpass industry standards by proving the effectiveness of the proposed model. In this manner, the SLP is implemented to mitigate the lack of order in storage, the 5S to address the inappropriate location of tools and the Poka Yoke to reduce the generation of waste. To validate the model, a pilot test was conducted for the 5S and Poka Yoke, while the Arena Simulator software was used for the SLP. The results were positive, showing a labor productivity of 25.02 Kg/Sol, a 3.19% reduction in standard time per box of cinnamon that went through the processes of cleaning and packaging, a reduction of waste of 54.17%, a 55.02% reduction in cleaning time for cinnamon and an overall reduction in standard time of 5.35%.